Conditions for Successful Adaptation of Foreign Students in Ukraine - Severyn, N.; Cherniavska , S. (New Collegium, 2021)
The article is devoted to the problem of foreign students’ adaptation to the living and study conditions in Ukraine. A brief review and an analysis of scientific literature on the problem of studying the difficulties of the individual’s adaptive processes and determining the nature of the phenomenon and duration of the ‘culture shock’ effect on foreigners are carried out. The aim of the work is to find out the foreign students’ particular features that affect the quality of academic performance, and factors that contribute to the effective and comfortable adaptation of foreigners in conditions of stay in a foreign culture. International education faculty of NTU "KhPI" is an important stage in the system of training foreign qualified specialists for foreign countries. Therefore, curators need to properly organize the gradual entry of foreign students into a foreign language culture, help them get used to the living and socio-cultural conditions of Ukraine, the new education system and the new language. Getting students into a new cultural environment always causes them "culture shock". In this regard, the lecturer-curator needs to pay considerable attention to solving this problem and finding new forms and methods of work to successfully overcome it. The lecturer’s assistance in the process of adapting international students to new socio-cultural conditions is the main factor that significantly affects the success of students and the effectiveness of the educational process. Preparing textbooks and manuals contributes to the development of communication skills and the formation of ideas about the cultural realities of the country of the studied language. Successful adaptation is facilitated by thematic lessons, writing abstracts for the student scientific conference "Ukraine and the World" under the curator’s supervision, preparing presentations and speeches, vocational-guidance events, etc. City presentation tours, trips to the Maxim Gorky Central Park for Culture and Recreation, visiting the opera and ballet theater, viewing art and other exhibitions, getting acquainted with Ukrainian dishes, etc speed up the cultural adaptation of foreign students. A successful combination of academic and extracurricular activities can significantly facilitate the entry of foreigners into the Ukrainian socio-cultural environment.